Hybrid Ideals of a Near algebra (European Journal of Pure and Applied Mathematics, 2025)
This study intends to learn hybrid ideals of a near algebra. It is briefed with the proper definitions and theorems of the hybrid ideal of a near algebra, near algebra homomorphism, Cartesian product of hybrid ideals of a near algebra and the coset of hybrid ideal of a near algebra. It has been demonstrated that an onto homomorphic image of a hybrid ideal of a near algebra is the hybrid ideal of the near algebra.
Keywords: Hybrid structure; Near algebra; Ideal; Hybrid field